Future of nature, our future. A preregistered report on future time perspective, social value orientation, and pro-environmental outcomes based on data from Poland and Sweden - Nowakowska, Iwona; Rönnlund, Michael (Frontiers in Psychology, 2023)
The objective of the study was to examine the role of social value orientation and future time perspective to account for individual differences in pro-environmental behaviors, intentions, and opinions about the link between pro-environmental action and pandemic threat (3 separate models) in Polish and Swedish samples expected to differ in rate of pro-environmental behaviors (higher in Sweden). We hypothesized that for Poland, future time perspective would be linked to pro-environmental outcomes only when social value orientation is average or high. In contrast, for Sweden, we expected a significant link between these variables regardless of social value orientation. In total, 301 (150 Polish, 151 Swedish) participants completed online surveys via Prolific.co research panel. We controlled for individualizing/binding moral foundations, present time perspectives, and selected demographic variables in the analyses. In line with expectations, the individualizing moral foundations were a significant predictor across all three models. The data did not support our focal hypothesis regarding the interaction between future time perspective and social value orientation. For pro-environmental behaviors in the past six months, the future time perspective was a predictor only when social value orientation was low. It suggests that when encouraging more competitive (compared to altruistic) people to behave in a green way, it might be crucial to underline the future consequences and benefits, consistent with the future time perspective. The pro-environmental campaigns could, therefore, highlight how green behavior may bring personal gains in the future, which are typically valued by individualistic people, such as savings or social status.